ANALISA VARIASI PUTARAN PADA MESIN ROLL PEMBENTUK PLAT PROFIL TERHADAP HASIL PENGEROLAN PLAT 1 MM - Firmansyah, Muhammad Rizky; Yulfitra, Yulfitra; zulkifli, zulkifli; Basyir, Abdul (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2017)
Plate roll machine is a tool used to make materials into other forms as the basic material for making gutters. To get good rolling quality and in accordance with the basic ingredients for making machines. The question of roll machine rolls is done to analyze the yield and rolling quality. From the observation of 6061-O aluminum plate with 23 rpm (n) rotation, the results of rolling are 8 pieces, 36 rpm (n) rotation, 9 pieces of rolling results, and 44 rpm yield (n) rolling produces a wave of 11 pieces. The results of rolling with a slight wave defect and will be used as the basic material for making gutters.